Penerapan Teknologi Inovasi Pembuatan Pupuk Biosaka di Desa Ellak Laok Kecamatan Lenteng Kabupaten Sumenep - Suprapti, Isdiana; Wulandari, Silvi Eka; Agustina, Nur W.D; Putri, Maduri Diana; Arifin, Ayu; Toha, Eltsabitah; Romadhoni, Abdullah Husain (LPPM Universitas Trunojoyo Madura, 2023)
Fertilizer is a material that provides essential elements that can be added to the soil to support plant growth. Fertilizers can be divided into two, namely organic fertilizers and inorganic fertilizers. The use of chemical fertilizers from time to time has increased. Low soil fertility due to chemical compounds can cause excessive soil pollution if used continuously and become a major problem in agricultural cultivation. In addition, other problems experienced by farmers are fertilizer subsidies from the government, while the majority of farmers are dependent on chemical fertilizers. Biosaka is one of the renewable technology systems for modern organic agriculture in the form of bio-technology. The method used in collecting data is through surveys, using a technical approach (community development) through several stages, including: discussion group forums, mentoring to overall training packaged in community empowerment. The series of stages in the training of making biosaka fertilizers, the stages include discussion group forums with the surrounding community, mentoring, training, making biosaka fertilizers. Through the manufacture of biosaka fertilizers have a good impact and can improve the economy. Therefore, there is a need for direct guidance for local farmers so that their dependence on chemical fertilizers can change. Direct guidance can be through actions taken by local agricultural extension workers, the government or student service programs.